PERANAN GURU SEKOLAH MINGGU SEBAGAI PEMBIMBING ROHANI ANAK USIA 5-11 TAHUN DI PERSEKUTUAN DOA ANAK PUTRI TUJUH BATAM - Purba, Gomgom; Nainggolan, Jalson (JURNAL IMPARTA, 2025)
This study aims to determine the Role of Sunday School Teachers as Spiritual Guides in Children's Prayer Fellowship for Children's Worship Interests. The role of Sunday school teachers in educating and guiding children is a very important foundation for forming their character into children who fear God. The research method used is a qualitative research method by conducting interviews with 6 participants. The results of the study are that Sunday school teachers' understanding of the importance of building positive character in children aged 5-11 years is very deep and involves various psychological, social, and spiritual dimensions. The form of involvement of children aged 5-11 years in the Seven Batam Children's Prayer Fellowship in building positive character in children is very varied and reflects a conscious effort in building positive character through a comprehensive and interactive spiritual experience. The role of Sunday school teachers in building positive character in children aged 5-11 years in the Seven Batam Children's Prayer Fellowship involves many responsibilities, teachers are not just teachers or activity facilitators, but they are educators who are committed to guiding children in the process of character formation that is thick with moral and ethical values ​​in the context of religion.